Modeling determinants of stunting among children under five years in Urban Areas - Fibrianti, Fibrianti; Palupi, Fitria Hayu; Mentari, Witri Dewi; Setiyadi, Agung; Sutriyawan, Agung (International Journal of Public Health Science (IJPHS), 2025)
Child stunting remains a global public health problem. Compared to other middle-income countries, Indonesia is one of the countries with a high prevalence of stunting. This study aims to identify predictive indices and analyse the determinants of stunting in children under five in urban areas. Case control design was conducted on 420 (210 cases and 210 controls). Simple random sampling and side proportional techniques were used for sampling. Structured questionnaires were used to collect data through interviews and anthropometric measurements. Multivariable binary logistic regression analysis and statistical significance expressed at 95% CI, as well as receiver operating characteristic analysis were used. Mothers with low education (OR=1.6, 95% CI=1.0-2.6), fathers with no permanent job (OR=1.5, 95% CI=1.0-2.4), pregnancy interval less than 24 months (OR=1.6, 95% CI=1.0- 2.6), family size of five or more (OR=2.1, 95% CI=1.3-3.3), income below minimum household income (OR=1. 7, 95% CI=1.0-2.8), not exclusively breastfed (OR=2.1, 95% CI=1.1-3.7), not fully immunised (OR=2.1, 95% CI=1.0-4.4), low birth weight (OR=2.3, 95% CI=1.2-4.5), and a history of disease (OR=2.0, 95% CI=1.0-3.8) were determinants of stunting. The most dominant determinant of stunting in children under five years old is low birth weight. Therefore, strategies and programmes are aimed at early prevention efforts, by increasing awareness to change community behaviour regarding improving maternal nutrition since pregnancy.